Hinduism, yoga and Indian culture: the unpublished writings of K. Satchidananda Murty - Murty, Kotta Satchidananda (Taylor & Francis Group, 2024)
"This volume is a collection of K. Satchidananda Murty's unpublished writings. It presents Murty's views on Hinduism, Indian culture, and Yoga. Murty traces the etymological origins of the term 'dharma' and discusses its contemporary relevance to argue that politics cannot be severed from ethics and spirituality. He evaluates the similarities and differences between Yoga and psychoanalysis, samādhi and hypnosis, Hatha Yoga and athletics, and Yoga and Shamanism. The volume also includes Murty's essays on caste mobility, the notion of unity of India, Hindu metaphysics, and the concept of Indian philosophy. An important contribution, the book assesses K. Satchidananda Murty's contribution to philosophy during sixty-one years of his engagement with active writing and teaching. It will be of great interest to scholars, teachers, and students of Indian philosophy, Hindu philosophy, comparative philosophy, Asian Philosophy, religious studies, political studies and South Asian studies"--